Brazing of super-hard AlMgB14–TiB2 ceramic to 304 stainless steel with AgCuTi filler alloy. (March 2022) - Song, X.G.; Lei, Y.; Fu, W.; Luo, Z.K.; Li, H.L.; Long, W.M.; Hu, S.P.
Abstract: In this paper, super-hard AlMgB14 –TiB2 composite ceramic is brazed to 304 stainless steel by using an AgCuTi foil at 820 °C–910 °C for 10 min. The typical microstructure of the joint brazed at 850 °C for 10 min is 304 steel/σ-Fe/Fe2 Ti/FeTi/Ti[Cu, Fe]ss/Ag(s, s)+TiCu4 +Cu(s, s)/Cu[Ti, Al]ss + TiB whiskers/AlMgB14 –TiB2 . The formation of Cu[Ti, Al]ss + TiB whisker layer at brazing filler/AlMgB14 interface is mainly ascribed to the reaction between AlMgB14 and active Ti. With the increase of brazing temperature, the width of the brazing seam drops remarkably, while the share of Cu (s, s) in the brazing seam is increased. The maximum shear strength of joint is ∼ 47.9 MPa when brazing at 880 °C for 10 min, the fracture occurs in the AlMgB14 –TiB2 substrate adjacent to the brazing seam. Highlights: A Cu[Ti, Al]ss + TiB whisker reaction layer generates at the brazing filler/AlMgB14 interface. The joint with a maximum shear strength of 47.9 MPa is obtained at 880 °C for 10 min. Fracture mainly occurs at the AMBT substrate beside the brazing seam.